Safer scoring? Cryptomarkets, social supply and drug market violence - Barratt, Monica; Ferris, J.; Winstock, A. (Elsevier BV, 2015)
Background: Cryptomarkets are digital platforms that use anonymising software (e.g. Tor) and cryptocurrencies (e.g. Bitcoin) to facilitate trade of goods and services, most notably illicit drugs. Cryptomarkets may reduce systemic violence compared with in-person drug trading because no face-to-face contact is required and disputes can be resolved through a neutral third party. In this paper, we describe the purchasing behaviour of cryptomarket users and then compare the self-reported experiences of threats, violence and other drug-market concerns when obtaining drugs from cryptomarkets with obtaining drugs through friends, known dealers and strangers. Methods: The Global Drug Survey was completed in late 2014 by a self-selected sample who reported accessing drugs through cryptomarkets in the last 12 months (N = 3794). Results: Their median age was 22 years and 82% were male. The drug types most commonly obtained through cryptomarkets were MDMA/Ecstasy (55%), cannabis (43%) and LSD (35%). Cryptomarket users reported using a median of 2 sources in addition to cryptomarkets to access drugs, the most common being in-person friendships (74%), in-person dealers (57%) and open markets/strangers (26%). When asked to nominate the main source they would use if cryptomarkets were unavailable, 49% nominated friends, 34% known dealers and 4% strangers. 'Threats to personal safety' (3%) and 'experiencing physical violence' (1%) were less often reported when using cryptomarkets compared with sourcing through friends (14%; 6%), known dealers (24%; 10%) or strangers (35%; 15%). Concerns about drug impurities and law enforcement were reported more often when using the alternative source, while loss of money, waiting too long and not receiving the product were more often reported when using cryptomarkets. Conclusion: Cryptomarkets are associated with substantially less threats and violence than alternative market types used by cryptomarket customers, even though a large majority of these alternatives were closed networks where violence should be relatively less common.